Hablun Minannas Wanita Bercadar (Studi Fenomenologi Interaksi Sosial Wanita Bercadar di Kecamatan Manggala Makassar) - Ramdani, Fauziah; Aswar, Aswar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
Cultural identity of women with veil in the concept of the development of relationship with social ernironment perpetually becomes pros-and-cons phenomenon due to its accordance with the comprehension of religious symbols that is the wering of veil. The objectives were to recognize and describe the empirical reality of habluminannas concept that is the process of social interaction of women with veil. To comprehensively and deeply achieve these objectives, the methodology employed was descriptive qualitative research with in-depth interviews and observations (field research) as data collection techniques. The results show that the concept of habluminannas, that is social interaction of women with veil, is based on the essence of each need in daily social life. The process of interacting with other individuals both within the family and people in general depends on the interests and needs of each. Social interaction within the family is divided into two those are interaction that shows flexibility in communication and behavior patterns, and interaction that is closed and bounded. In the community, the process of social interaction that is associative process shows the flexibility of women with veil in the patterns of cooperation among citizens and relatives, mutual respect, and respect for the values ​​of decency and politeness. On the other hand, the attitude of acceptance by community in general towards women wearing veil is still not prevalent due to the negative stigma against the use of veils.